2020
DOI: 10.4103/ijpsym.ijpsym_364_19
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine-induced Drug Reaction with Eosinophilia and Systemic Symptoms Syndrome

Abstract: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a rare condition affecting between 1 in 1,000 to 1 in 10,000 patients after exposure to associated drugs. [1] It is a life-threatening condition with a mortality rate of about 10%, which necessitates early identification and treatment. [2] We describe a case of DRESS syndrome secondary to the use of chlorpromazine in a female with paranoid schizophrenia, the diagnostic challenge encountered, and the successful treatment of the condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The regulation of blood within a normal range is crucial for maintaining homeostasis and carrying out its vital functions. In this study, rats treated with CPZ (30 mg/kg/d) for 56 days showed signs of anemia and changes in their blood composition, which are in line with previous studies [32] , [35] , [50] . These changes included alterations in RBC, erythropoietin, WBC, platelet count, PCV, Hb, neutrophil, lymphocyte, and a significant increase in MCV, MCH, and Eos levels.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The regulation of blood within a normal range is crucial for maintaining homeostasis and carrying out its vital functions. In this study, rats treated with CPZ (30 mg/kg/d) for 56 days showed signs of anemia and changes in their blood composition, which are in line with previous studies [32] , [35] , [50] . These changes included alterations in RBC, erythropoietin, WBC, platelet count, PCV, Hb, neutrophil, lymphocyte, and a significant increase in MCV, MCH, and Eos levels.…”
Section: Discussionsupporting
confidence: 92%
“…The alterations in MCV and MCH, both of which measure the average size of RBCs and the amount of hemoglobin known to transport oxygen in the RBCs respectively, observed in hematological research indicate that CPZ-induced a hemolytic anemic condition linked to RBC disorders [29] , and is in line with previous clinical findings [40] . Chronic life-threatening hematological RBC disorders such as agranulocytosis, have been largely reported in psychotic patients treated with antipsychotic drugs, notably CPZ [32] , [35] , [50] . Although the specific management of anemic-like conditions includes the use of blood transfusion and iron-based supplements, application of naturally occurring compounds with antioxidant functions has increased in recent years owing to the role of oxidative stress in the pathogenesis of hemolytic blood disorders [30] , [72] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Very few reports, however, exist in psychiatric literature. [3][4][5][6] PubMed-based MeSH search [("Drug Hypersensitivity Syndrome"[Majr]) AND "Psychotropic Drugs" [Majr]] and search terms restricted to the title/abstract returned less than 10 case reports, inclusive of cross-reference search.…”
Section: Drug Reaction With Eosinophilia and Systemic Symptoms (Dress) Syndrome In A Patient With Bipolar Disorder: A Case Reportmentioning
confidence: 99%